Hepatic iNKT cells produce type 2 cytokines and restrain antiviral T cells during acute hepacivirus infection - Raus, Svjetlana; Lopez-Scarim, Jarrett; Luthy, Joshua; Billerbeck, Eva (Frontiers in Immunology, 2022)
Chronic hepatitis C virus (HCV) infection is a curable disease, but the absence of a vaccine remains a major problem in infection prevention. The lack of small animal models and limited access to human liver tissue impede the study of hepatic antiviral immunity and the development of new vaccine strategies. We recently developed an immune-competent mouse model using an HCV-related rodent hepacivirus which shares immunological features with human viral hepatitis. In this study, we used this new model to investigate the role of invariant natural killer T (iNKT) cells during hepacivirus infection in vivo. These cells are enriched in the liver, however their role in viral hepatitis is not well defined. Using high-dimensional flow cytometry and NKT cell deficient mice we analyzed a potential role of iNKT cells in mediating viral clearance, liver pathology or immune-regulation during hepacivirus infection. In addition, we identified new immune-dominant MHC class I restricted viral epitopes and analyzed the impact of iNKT cells on virus-specific CD8+ T cells. We found that rodent hepacivirus infection induced the activation of iNKT cell subsets with a mixed NKT1/NKT2 signature and significant production of type 2 cytokines (IL-4 and IL-13) during acute infection. While iNKT cells were dispensable for viral clearance, the lack of these cells caused higher levels of liver injury during infection. In addition, the absence of iNKT cells resulted in increased effector functions of hepatic antiviral T cells. In conclusion, our study reports a regulatory role of hepatic iNKT cells during hepacivirus infection in vivo. Specifically, our data suggest that iNKT cells skewed towards type 2 immunity limit liver injury during acute infection by mechanisms that include the regulation of effector functions of virus-specific T cells.